DESIGN AND SURVEY OF A MODULAR CLINICAL APPLICATION VENTILATOR - B. , Sai Pavan Krishna; Y. , Bhaskar Rao (International Journal of Psychosocial Rehabilitation, 2020)
The cost of treatment for ventilator-reliant clinicians is a huge hindrance not just for their relatives but also for preventive structures in particular. The use of high-frequency ventilators has recently been illustrated to minimize lung arrest due to decreased flow of circulation. The devices pre-owned today, however, are voluminous, inordinate, and mostly for use in hospice environments. A compact, low-density high-frequency ventilator is a pressing necessity that will give patients transitional rehabilitation among hospital stays and effective recovery. This research introduces the concept of a high-frequency portable ventilator as well as an analysis of it’s virtually for other medical parameters. By combining highly developed technological and industrial facilities, we build a portable high-frequency ventilator for the needs of reserved outpatients with tunable air distribution frequency, pressure applied, and volume of air. For relaxation and sensitivity performance, a higher-frequency handheld ventilator with a virtual device and closed-loop system is implemented. In animal experiments, the efficacy of CO2 downpour using the schemed ventilator was validated.